Conserved FcγR- glycan discriminates between fucosylated and afucosylated IgG in humans and mice. (February 2018) - Dekkers, Gillian; Bentlage, Arthur E.H.; Plomp, Rosina; Visser, Remco; Koeleman, Carolien A.M.; Beentjes, Anna; Mok, Juk Yee; van Esch, Wim J.E.; Wuhrer, Manfred; Rispens, Theo; Vidarsson, Gestur
Graphical abstract: Highlights: The N162 glycan is conserved between the orthologous human FcγRIIIa and mouse FcγRIV. This glycan endows the receptors to discriminate between fucosylated and afucosylated IgG. Human afucosylated IgG/FcγRIIIa affinity is further directed by additional galactosylation. Mouse afucosylated IgG/FcγRIV affinity remains unaffected by additional galactosylation. Abstract: The binding strength between IgG and FcγR is influenced by the composition of the N-linked glycan at position N297 in the Fc-domain of IgG. Particularly, afucosylation increases the binding affinity of human IgG1 to human FcγRIIIa up to ∼20 fold, and additional galactosylation of the afucosylated IgG increases the affinity up to ∼40 fold. The increase in affinity for afucosylated IgG has previously been shown to depend on direct carbohydrate-carbohydrate interactions between the IgG-Fc glycan with an N-linked glycan at position 162 unique to hFcγRIIIa and hFcγRIIIb. Here we report that the N162 glycosylation site is also found in the orthologous mouse FcγR, mFcγRIV. The N162-glycan in mFcγRIV was also responsible for enhancing the binding to mouse IgG with reduced fucose similar to hFcγRIIIa. However, unlike hFcγRIIIa, mFcγRIV did not bind more avidly to IgG with increased galactose and reduced fucose. Overall, these results suggest the N162-glycan in the human FcγRIII family and its orthologous mouse FcγRIV to be functionally conserved.